Mobile application: physical therapy interventions for frail older adults. - de Melo Moreira, Wagner Elias; Detomi Rodrigues, Gustavo; de Carvalho Mello, Jorge Luiz; Maia, Paulo Roberto; Sebba Tosta de Souza, Diba Maria (Fisioterapia e Pesquisa)
The aim of this study was to build and validate an algorithm and develop a software for the multidimensional diagnosis of functional clinical vulnerability and physical therapy for older adults. This is an analytical and observational study applied in technological production, based on software engineering and user-centered design. The algorithm was developed based on studies in health databases, validated by 13 physical therapists and the software was built using the JAVA language from the algorithm's conversion. The Delphi technique and statistical analysis via the Content Validity Index (CVI) were used to validate the algorithm. The consensus was reached in the first evaluation round and the agreement between judges by the CVI was 1.0. The "Gerontofisio" mobile application was built for use on smartphones and tablets and registered at the Brazilian National Institute of Industrial Property number: BR512020002269-3; the application consists of 34 screens that guide gerontological physical therapists in decision making, serving as a support tool in the applied fields in health, health administration, illness, medical assistance and diagnostic therapy. The algorithm was built and validated, the mobile application software for the multidimensional diagnosis of clinical functional vulnerability and physical therapy treatment in older adults was developed and is valid in the field of physical therapy and should contribute to physical therapists and older adults.